Profile of Diarrheal Patients Aged Less than Five Years Old Hospitalized in Dr. Soetomo General Hospital Surabaya in 2016-2018 - Nathanael Jordan; I Gusti Made Reza Gunadi Ranuh; Gadis Meinar Sari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Diarrhea is a collection of symptoms in the form of decreased stool consistency accompanied by more than normal frequency of defecation. Diarrhea is the second largest cause of death in children under five years old. In 2010, East Java was ranked first in the frequency of outbreaks in Indonesia. This study described the profile of diarrhea patients in children less than 5 years old in the Children's Ward of Dr. Soetomo General Hospital Surabaya in 2016-2018. Dr. Soetomo General Hospital Surabaya was chosen for data collection because it is one of the main referral hospitals in Indonesia, thus it has diverse cases. This study aimed to describe the profile of diarrhea patients in children less than 5 years old in the Children's Ward of Dr. Soetomo General Hospital Surabaya in 2016-2018.Methods: This study was a retrospective study by assessing the patient's medical record and analyzed descriptively.Results: There were 650 patients (425 male and 225 female), at most 6-11 months (34.6%). Most patients were classified as malnourished (45.4%). The type of diarrhea was dominated by acute watery diarrhea (94.8%). Mild-to-moderate dehydration (84.2%) was found in most patients. The comorbidities were found in 83.4% of patients, with malnutrition (45.4%) and febrile seizures (30.3%) as the most common contributors. The therapy used was intravenous rehydration (99.7%), antibiotics (45.7%), zinc (98.2%), and probiotics (96.3%).Conclusion: Most diarrhea patients in this study were male, aged 6-11 months, mild-to-moderate dehydration, malnourished, suffering from acute water diarrhea, accompanied by comorbidities, and treated with intravenous rehydration.